Efektivitas Penggunaan Media Pembelajaran Interaktif Nearpod pada Mata Pelajaran Bahasa Indonesia - Ramanda Oktaviani; Didah Nurhamidah (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2023)
This study aims to determine how effective the use of Nearpod media is based on motivation and learning outcomes of 11th grade students of Beauty Vocational School Taruna Terpadu 2. The research method used is a qualitative descriptive method supported by quantitative data. The data obtained in this study were based on the results of the scores contained in the Nearpod application and the results of manual tests (pretest – posttest) and written questionnaires (questionnaire) conducted online. The subjects of this study were 11th grade beauty students at Vocational School Taruna Terpadu 2 Bogor, totaling 14 people. Based on the results and discussion in this study, in the use of Nearpod media, student motivation and learning outcomes have increased, so it can be concluded that the use of Nearpod learning media is effectively used in the Indonesian Language class 11 Beauty class at Vocational School Taruna Terpadu 2 Bogor.